PENGARUH BAKTERI ENDOFIT ASAL AKAR KAYU KETAPANG HUTAN (Terminalia catappa) TERHADAP PERTUMBUHAN DAN PRODUKSI PADI SAWAH (Oryza sativa) - Ambarwati, Ririn; Matinahoru, Johan; Hadijah, Miranda (PT. BARRINGTONIA ASIATICA LESTARI, 2025)
This study aimed to determine the effect of biofertilizer containing endophytic bacteria from the roots of Indian almond trees (Terminalia catappa) on the growth and yield of lowland rice (Oryza sativa). The experiment used a completely randomized design (CRD) with three treatments: NPK fertilizer, endophytic bacterial biofertilizer, and a combination of both, each with three replications. Observed parameters included root dry weight, dry grain weight, and dry rice weight. The results showed that the endophytic bacterial treatment significantly increased all measured parameters compared to NPK and the combination treatments. Treatment A2 (endophytic bacteria) produced the highest values across all variables. These findings indicate that endophytic bacteria from the roots of Terminalia catappa have great potential as a biofertilizer to support sustainable and environmentally friendly rice cultivation.